Development and application of an algorithm to estimate the effective energy of x-rays on conventional mammography - Fiorela Merma Velasco; Mariela Bellotti; Pablo Andres (Brazilian Journal of Radiation Sciences, 2024)
Mammography is a radiation medical exam, which makes detection of mammary microcalcifications possible at an early stage. The dose received by the patient’s breast is known as the average glandular dose, which is considered a quality control indicator. Estimation of this parameter implies knowing the effective energy of the x-ray beam delivered. This is the case when thermoluminescent dosimetry is the method of choice. The algorithm developed to discriminate the x-ray energy the mammography patient has been exposed to while undergoing routine procedures, applies two thermoluminescent dosimeters, one of them filtered by a 1 mm thick aluminum layer. The effective energy of the x-ray beam and the correction factor are obtained by knowing the relation between the filtered and non-filtered dosemeters readout. This algorithm was then used to estimate the average glandular dose following the IAEA TRS 457 protocol. The dose values computed were compared with the international diagnostic reference levels suggested by the technical literature.